Maternity nursing care - Littleton-Gibbs, Lynna Y.; Engebretson, Joan C. (Delmar, Cengage Learning, 2013)
Maternity Nursing Care, second edition, delivers all the core components of maternity nursing, along with in-depth study features to help you develop and enhance your analytical skills. Starting with women's health issues and pregnancy care, the chapters progress through labor and childbirth, postpartum care, and newborn development, addressing the nursing considerations for both normal and high-risk scenarios where appropriate. Written from a nursing perspective, Maternity Nursing Care, second edition, emphasizes overall patient care as opposed to medical treatment alone, and it illustrates the critical importance of fostering the nurse-patient relationship. Features: all chapters contain the most recent standards, guidelines, and evidence for nursing practice, along with ethical and legal considerations to consider during patient care, enabling you to keep pace with changes in the health care field; every chapter contains Reflections and Critical Thinking sections with detailed case scenarios involving different care settings nad various nursing roles, offering multiple opportunities to hone collaboration, decision making, and analytical skills; cultural negotiation boxes highlight the importance of understanding the influence of culture on a patient's health beliefs and practices by walking through various scenarios and possible resolutions; seeking evidence-based practice features encourage a knowledge-based practice by offering insight into new research, approaches, and technology; in-text nursing process sections give you the foundation for sound clinical care, and case study/care plans encourage the critical thinking skills necessary to apply these theories to real-life practice; full-color photo stories depict procedures and nursing care, emphasizing clinical excellence and the nurse-patient relationship, to help you imagine yourself in maternity nursing roles